Multiple Sclerosis: Impact on Oral Hygiene, Dysphagia, and Quality of Life - Covello, Francesco (Int J Environ Res Public Health, 2020)
Multiple sclerosis (MS) is an autoimmune disease in which the immune system reacts by damaging the central nervous system, specifically myelin and oligodendrocytes. It is the most debilitating neurological disease among young adults, causing personal, familiar, social, and professional limitations. Multiple sclerosis can cause disturbances in the orofacial district, due to a demyelination process on the nerves of the head and neck district. The aim of this study was to evaluate the oral health status, dysphagia, and quality of life of patients affected by MS. For this study, 101 patients aged between 12 and 70 (47 males, 54 females) affected by MS were selected, and three questionnaires were handed out and anonymously filled in by them: An oral hygiene test, DYMUS (DYsphagia in MUltiple Sclerosis), and IOHIP-14 (Italian version Oral Health Impact Profile). Through the analysis of the questionnaires it was possible to observe pathological conditions, such as gingival inflammation, xerostomia, dysphagia, neuralgia, and dysarthria. Through the analysis it was possible to outline how the roles of a medical team, composed of a dentist, otolaryngologist, and dental hygienist, are fundamental in coping with other medical figures, during the whole development of the diseases, as well as to prevent possible complications.